2015
DOI: 10.1161/strokeaha.114.008007
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Legislation Impacts Distribution of Certified Stroke Centers in the United States

Abstract: This study included only those that were categorized as general hospitals with emergency departments. Rehabilitation, geography, pediatric, long-term care, and federal government hospitals (Veterans and military hospitals) were excluded. For hospitals with multiple sites, the entry in Background and Purpose-The number of certified primary stroke centers (PSCs) have increased dramatically during the past decade in the United States We aimed to understand the factors affecting PSC distribution in the United Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…It is important to keep in mind that these practices remain suboptimal even in HIC hospitals, especially in rural areas. For example, a 2013 study conducted in the United States revealed that the number of hospitals that have organized stroke unites varied widely across the states, ranging from 4% in Wyoming to 100% in Delaware, with an overall median of 25% [20]. This confirms the continuous need to improve and build on our knowledge of implementing evidence-based practices for stroke care across all country income groups.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to keep in mind that these practices remain suboptimal even in HIC hospitals, especially in rural areas. For example, a 2013 study conducted in the United States revealed that the number of hospitals that have organized stroke unites varied widely across the states, ranging from 4% in Wyoming to 100% in Delaware, with an overall median of 25% [20]. This confirms the continuous need to improve and build on our knowledge of implementing evidence-based practices for stroke care across all country income groups.…”
Section: Discussionmentioning
confidence: 99%
“…The literature provides evidence that a top-down approach improves access to stroke care. 4,5 Introduction of relevant legislation in some American states substantially increased the proportion of hospitals with certified primary stroke centers, compared with states without such legislation (median: 43% and 13% of hospitals, respectively; p < 0.001). 4 Stroke legislation was also associated with increased availability of access to certified primary stroke centers.…”
mentioning
confidence: 99%
“…4,5 Introduction of relevant legislation in some American states substantially increased the proportion of hospitals with certified primary stroke centers, compared with states without such legislation (median: 43% and 13% of hospitals, respectively; p < 0.001). 4 Stroke legislation was also associated with increased availability of access to certified primary stroke centers. 4 Elsewhere, organized systems such as certification (Europe) 6 and high-level government overview (Canada) 7 are also used to formalize stroke care.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…34 In addition, geographic disparities in stroke centers exist with the majority of facilities located in large urban settings primarily in states with existing stroke legislation. 35 Therefore, health care policies implemented at a regional and national level will be necessary to increase the availability and distribution of stroke centers in the future. In comparison, there are more than 1,000 primary stroke centers (PSCs) in the United States, but less than half of these facilities offer around-the-clock mechanical thrombectomy.…”
Section: Figmentioning
confidence: 99%